Tourism, Trade and Domestic Welfare - Pasquale M. Sgro; Jean-Jacques Nowak; Mondher Sahli (Fondazione Eni Enrico Mattei (FEEM), 2004)
Tourism has been regarded as a major source of economic growth and a good source of foreign exchange earnings. Tourism has also been considered as an activity that imposes costs on the host country. Such costs include increased pollution, congestion and despoliation of fragile environments and intra-generational inequity aggravation. One aspect that has been ignored is the general equilibrium effects of tourism on the other sectors in the economy. These effects can be quite substantial and should be taken into account when assessing the net benefits of a tourism boom on an economy. This paper presents a model which captures the interdependence between tourism and the rest of the economy, in particular agriculture and manufacturing. We examine the effect of a tourist boom on structural adjustment, commodity and factor prices and more importantly resident welfare. An important result obtained is that the tourist boom may immiserize the residents. This occurs because of two effects. The first, a favourable effect due to an increase in the relative price of the non-traded good which is termed the secondary terms of trade effect. The second, a negative effect due to an efficiency loss that occurs in the presence of increasing returns to scale in manufacturing. If this second effect outweighs the first effect, resident immiserization occurs.
Keywords: F10; F22; 330; Tourism; Trade welfare; Tourismus; Wohlfahrtsanalyse; Landwirtschaft; Industrie; Theorie; Wirkungsanalyse